Drug management of oxidation-reduction state of the body in respiratory tract diseases (part 3) - A.E. Abaturov; A.P. Volosovets; T.P. Borysova (Zaslavsky O.Yu., 2018)
The review of the literature presents modern data on the group of antioxidant drugs - thiol-containing compounds. Their effect on the oxidation-reduction state in diseases of the respiratory system is shown.